The Effectiveness of Token Economy to Improve the Dicipline of TPQ Students - Mutiarini, Anggita Nuha; Idelitarahma , Khazana Firyal; Jamalludin, Muhammad; Kusumasari, Fitri (Jurnal Psikologi Teori dan Terapan, 2025)
Background: The discipline of TPQ students is relatively low, as evidenced by their behavior of disturbing their friends who are studying and their lack of focus, which often becomes a challenge in the learning process at TPQ. This hinders the effectiveness of learning. Objective: Evaluating the effectiveness of the economic token program as a means of improving student discipline in learning. Method: This study used a quasi-experimental design. The sample selected using purposive sampling and divided into two groups: control (n=10) and experimental (n=10). The intervention was carried out for 1 week, beginning with a pre-test and ending with a post-test. Data analysis was performed using JASP software with a non-parametric Mann-Whitney U test. Results: The findings showed a statistically significant difference in improvement scores between the experimental and control groups (W = 100,000, p < 0.001). The final results determined that the gain value of the experimental group was higher than that of the control group. Conclusion: Student discipline can be improved through token economy intervention and can be used as a classroom management strategy. Abstrak Latar Belakang: Disiplin siswa TPQ relatif rendah, sebagaimana terlihat dari perilaku mereka yang mengganggu teman-teman yang sedang belajar dan kurangnya fokus, yang sering menjadi tantangan dalam proses pembelajaran di TPQ. Hal ini menghambat efektivitas pembelajaran. Tujuan: Mengevaluasi efektivitas program token ekonomi sebagai sarana untuk meningkatkan disiplin siswa dalam pembelajaran. Metode: Penelitian ini menggunakan desain quasi-eksperimental. Sampel dipilih menggunakan sampling purposif dan dibagi menjadi dua kelompok: kontrol (n=10) dan eksperimen (n=10). Intervensi dilakukan selama 1 minggu, dimulai dengan pre-test dan diakhiri dengan post-test. Analisis data dilakukan menggunakan perangkat lunak JASP dengan uji Mann-Whitney U non-parametrik. Hasil: Temuan menunjukkan perbedaan yang signifikan secara statistik dalam skor peningkatan antara kelompok eksperimen dan kontrol (W = 100.000, p < 0,001). Hasil akhir menunjukkan bahwa nilai peningkatan kelompok eksperimen lebih tinggi daripada kelompok kontrol. Kesimpulan: Disiplin siswa dapat ditingkatkan melalui intervensi ekonomi token dan dapat digunakan sebagai strategi manajemen kelas.